Pengaruh Literasi Keuangan, Pengetahuan Investasi, dan Media Sosial Terhadap Minat Investasi Mahasiswa Melalui Motivasi Investasi - Kartikaningdyah, Ely; Zendrato, Gita Mentarina (Politeknik Negeri Batam, 2025)
This study is intended to evaluate how much influence financial literacy, investment knowledge, and social media have on students' interest in investing in the capital market, by considering the role of investment motivation as a mediating variable. This study involved 88 students using the IDX Investment Gallery at Batam State Polytechnic who were selected through purposive sampling technique. Using a quantitative approach and PLS-based SEM analysis with the help of SmartPLS 4 software, this study found that financial literacy and social media have a significant effect on investment motivation and interest, while investment knowledge does not show a significant effect. In addition, investment motivation is proven to mediate the relationship between financial literacy and social media on investment interest but does not mediate the relationship between investment knowledge.